High-strength and high-corrosion-resistance brazing aluminum alloy composite material for radiator and preparation method thereof
By using a core layer with specific element ratios and a modified carbonyl iron reinforced corrosion resistance layer in the radiator material, a high-strength, high-corrosion resistance brazed aluminum alloy composite material is formed, which solves the shortcomings in strength and corrosion resistance of traditional aluminum alloy pipes, and achieves higher material performance and service life.
Patent Information
- Application Number
- CN202411820127.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The aluminum alloy pipes used in traditional radiators still have room for improvement in strength and corrosion resistance, especially under the market's continuous improvement of material performance.
A high-strength, high-corrosion resistance brazed aluminum alloy composite material consisting of a brazing layer, a core layer and an anti-corrosion layer is used. The core layer contains elemental components with specific elements proportional, such as iron, copper, manganese, zirconium, etc. The anti-corrosion layer contains elements such as silicon, iron, manganese, zinc, titanium, zirconium, etc., and the corrosion resistance of the anti-corrosion layer is improved by modifying carbonyl iron.
It effectively improves the strength and corrosion resistance of composite materials, extends service life, and meets the market's demand for high-performance materials without increasing the thickness of the material.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of aluminum alloy materials, and in particular to a high-strength and high-corrosion-resistant brazed aluminum alloy composite material for a radiator and a preparation method thereof. Background Art
[0002] In recent years, the traditional radiator industry has faced huge challenges. The market has increasingly higher requirements for materials. While reducing the thickness of materials, it is also necessary to improve the strength and service life of materials.
[0003] For example, the aluminum alloy pipe used in the radiator has a thickness reduced from the original 0.28-0.3mm to 0.25-0.26mm, and the strength has increased from 150-160MPa to 190-200MPa. The material has also been replaced from traditional 3003 aluminum alloy to reinforced 3003mod aluminum alloy. This type of product uses a three-layer composite structure, brazing layer + core layer + anti-corrosion layer. However, with the increase in market demand and the development trend of using high-strength corrosion-resistant materials, the performance of the pipe needs to be further improved. Summary of the invention
[0004] In order to improve the strength of the composite material, the present application provides a high-strength and high-corrosion-resistant brazing aluminum alloy composite material for a radiator and a preparation method thereof.
[0005] The present application provides a high-strength and high-corrosion-resistant brazed aluminum alloy composite material for a radiator and a preparation method thereof, which adopts the following technical solutions: In the first aspect, the present application provides a high-strength and high-corrosion-resistant brazed aluminum alloy composite material for a radiator, which adopts the following technical solution: A high-strength and high-corrosion-resistant brazed aluminum alloy composite material for a radiator, comprising a brazing layer, a core layer and an anti-corrosion layer arranged in sequence, wherein the core layer comprises the following elemental components in weight percentage: iron 0.3-0.7%, copper 0.5-0.8%, manganese 1.4-1.8%, zirconium 0.1-0.15%, magnesium ≤0.05%, zinc ≤0.05%, titanium ≤0.05%, and the balance is aluminum and inevitable impurities; the anti-corrosion layer comprises the following elemental components in weight percentage: silicon 0.5-1.0%, iron 0.2-0.3%, copper 0-0.1%, manganese 1.4-1.8%, zinc 4.0-5.0%, titanium 0.01-0.03%, zirconium 0.07-0.12%, and the balance is aluminum and inevitable impurities.
[0006] By adopting the above technical solution and controlling the content of each element in the core layer, the comprehensive performance of the core layer can be effectively improved. Among them, the iron element can improve the overall hardness and strength of the core layer, and also has a positive effect on the thermal stability of the alloy. Copper can strengthen the core layer, thereby further improving the tensile strength and fatigue resistance of the core material. Manganese can also improve the strength of the core layer and has a positive effect on the plasticity of the prepared composite material. Zirconium can refine the grains, increase the recrystallization temperature, and play a role in corrosion resistance. At the same time, controlling the above elements within a certain ratio range can effectively improve the stability and comprehensive performance of the core layer, so that the prepared composite material has good strength and corrosion resistance. The anti-corrosion layer can further enhance the corrosion resistance of the composite material. At the same time, the mass ratio of each element in the anti-corrosion layer is limited, thereby further improving the overall comprehensive performance and strength of the anti-corrosion layer. Silicon is also added to the anti-corrosion layer, which can improve the fluidity of the anti-corrosion layer and increase its hardness to further improve the comprehensive performance of the anti-corrosion. The addition of manganese can make the anti-corrosion layer have good strength. The addition of zinc can reduce the electrode potential of the anti-corrosion layer. In actual use, the zinc-containing anti-corrosion layer and the copper-containing core layer form an in-situ battery due to the potential difference. The anti-corrosion layer is the anode. Through the principle of sacrificial anode and protection of cathode, it can prevent the core layer from being corroded before the anti-corrosion layer is completely corroded, thereby extending the overall service life of the composite material.
[0007] Preferably, the iron element in the anti-corrosion layer is derived from carbonyl iron, and the carbonyl iron is prepared by modification treatment, and the modification treatment method of the carbonyl iron comprises the following steps: The modifier is dissolved in a solvent, subjected to ultrasonic treatment to obtain a surfactant dispersion, carbonyl iron powder is added to the surfactant dispersion, stirred at a certain temperature for a certain time to react, washed and dried to obtain prefabricated modified carbonyl iron; polydimethylsiloxane is added to n-heptane, subjected to ultrasonic treatment to obtain a mixed solution, and then the prefabricated modified carbonyl iron is added to the mixed solution, stirred, washed and dried to obtain modified carbonyl iron.
[0008] By adopting the above technical scheme, after carbonyl iron is added to the anti-corrosion layer as an iron element, the stability of the anti-corrosion layer can be effectively improved. After the carbonyl iron is modified with a modifier, the overall corrosion resistance of the carbonyl iron can be further improved. At the same time, the surface energy of the carbonyl iron particles can be reduced, so that the modified carbonyl iron is in a stable state. At the same time, the lipophilic group of the modifier forms a spatial barrier on the surface of the carbonyl iron, reducing the phenomenon of particle re-agglomeration. After being treated with polydimethylsiloxane, the amino group on the surface of the glycine-modified powder and the terminal hydroxyl group of the polydimethylsiloxane undergo dehydration condensation reaction, so that the polydimethylsiloxane is further coated, thereby further improving the overall hydrophobicity and corrosion resistance of the carbonyl iron. Therefore, the dispersion performance, stability performance and corrosion resistance of the carbonyl iron after modification with the modifier are improved, so the comprehensive performance of the corrosion-resistant layer is improved.
[0009] Preferably, the modifier includes any one of hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate and glycine.
[0010] By adopting the above technical scheme, the above modifiers all contain hydrophobic groups. After the carbonyl iron is modified by the above modifiers, the surface contact angle of the carbonyl iron can be increased, playing a hydrophobic role, thereby improving the dispersibility of the carbonyl iron in the system. At the same time, the absolute impedance of the carbonyl iron modified by the modifier can be improved, and the corrosion potential of the powder moves positively. Therefore, the modified carbonyl iron improves the overall corrosion resistance of the system, thereby improving the corrosion resistance and stability of the composite material.
[0011] Preferably, the mass ratio of the modifier, carbonyl iron and polydimethylsiloxane is 1:(2.1-2.2):2.5.
[0012] By adopting the above technical solution, the mass ratio of the modifier, carbonyl iron and polydimethylsiloxane is preferably within the above range, which can further improve the comprehensive performance of the modified carbonyl iron.
[0013] Preferably, the reaction time for preparing the prefabricated modified carbonyl iron is 1-2 h.
[0014] Preferably, the reaction temperature during the preparation of the prefabricated modified carbonyl iron is 57-63°C.
[0015] By adopting the above technical solution, the reaction time and reaction temperature of the carbonyl iron modification treatment are preferably within the above range, which can further enhance the coating effect of the modifier on the carbonyl iron, thereby further enhancing the performance of the modified carbonyl iron.
[0016] Preferably, the anti-corrosion layer further comprises the following elements in percentage by weight: 1.07-1.27% magnesium and 0.04-0.06% scandium.
[0017] By adopting the above technical solution, magnesium can effectively improve the corrosion resistance of the alloy as a whole after adding magnesium to the anti-corrosion aluminum alloy. At the same time, magnesium has good mechanical properties. After adding, it can improve the hardness and strength of the alloy as a whole, so that the strength of the anti-corrosion layer is further improved. The addition of scandium can effectively inhibit the precipitation of β phase, and can significantly improve the corrosion resistance of the alloy while improving the mechanical properties. After the two are combined, they can synergistically improve the strength and corrosion resistance of the system with zinc and zirconium. However, too much magnesium will affect the plasticity and corrosion resistance. It is preferred that the magnesium content and the scandium content are within the above range. After combining with the zinc and zirconium in the system, the oxygen adsorbed on the anode surface after polarization forms a dense oxide film, which effectively prevents the corrosion of the anti-corrosion layer and further improves the overall corrosion resistance and stability of the system.
[0018] In a second aspect, the present application provides a method for preparing a high-strength and high-corrosion-resistant brazed aluminum alloy composite material for a radiator, using the following technical solution: A method for preparing a high-strength and high-corrosion-resistant brazing aluminum alloy for a radiator comprises the following steps: The materials of the brazing layer, the core layer and the anti-corrosion layer are melt-casted according to the proportion, and then milled respectively after melting and casting. The milled brazing layer and the anti-corrosion layer are heated respectively, and then hot-rolled respectively to obtain the brazing prefabricated layer and the anti-corrosion prefabricated layer respectively. After cooling, the brazing prefabricated layer, the core prefabricated layer and the anti-corrosion layer are stacked in sequence, and the brazing layer prefabricated layer and the anti-corrosion layer prefabricated layer are fixed on both sides of the core layer prefabricated layer by argon arc welding, and the two ends are tied with steel strips to obtain a composite ingot; the composite ingot is rolled in a hot rolling mill, and then rolled by a cold rolling mill to obtain a semi-finished coil, the edge cracks, burrs and other parts of the semi-finished coil are cut off, and then rolled again by a cold finishing mill to obtain a coil of the final finished thickness, and then the coil surface is cleaned of oil, dirt and debris by a stretch bending and straightening machine, and finally annealed in an annealing furnace, and cut after cooling to obtain an aluminum alloy composite material.
[0019] Preferably, the rolling process of the composite ingot in a hot rolling mill specifically comprises the following steps: The middle part of the steel strips bundled at both ends of the composite layer is cold pressed, and the cold pressing direction is from the middle to both ends, wherein the cold pressing rolling speed is 20-30m / min, and the rolling is performed 3-5 times.
[0020] By adopting the above technical scheme, cold pressing is carried out before heating the composite layer. Through small reduction and slow rolling, the brazing layer, the anti-corrosion layer and the core layer can be initially composited, which effectively reduces the deviation and movement of the composite layer during formal hot rolling. At the same time, the air in the gap of the composite layer can be fully discharged, thereby reducing the phenomenon that the air cannot be completely discharged due to the excessively fast rolling speed during formal hot rolling, and finally the air remains in the middle of the composite layer to form bubbles, and the occurrence of defects in the finished product, thereby effectively improving the stability of the product.
[0021] In summary, the present application includes at least one of the following beneficial technical effects: 1. In the present application, the brazing layer, the core layer and the anti-corrosion layer are sequentially arranged to prepare the aluminum alloy composite material. At the same time, the content of each element in the core layer is controlled, which can effectively improve the overall hardness and strength of the core layer, and also promote the thermal stability of the alloy. Through the addition and proportion of each component, the composite material can withstand more external forces, and the brazed aluminum alloy composite material has good corrosion resistance, thereby improving the comprehensive performance of the composite material; the proportion content of each element in the anti-corrosion layer is limited, thereby further improving the overall comprehensive performance and strength of the anti-corrosion layer. In actual use, the zinc-containing anti-corrosion layer and the copper-containing core layer form an in-situ battery due to the potential difference. The anti-corrosion layer is the anode. Through the principle of sacrificial anode and protection of cathode, it can prevent the core layer from being corroded before the anti-corrosion layer is completely corroded, thereby extending the service life of the composite material as a whole; 2. The iron element in the anti-corrosion layer comes from carbonyl iron. After the carbonyl iron is modified by the modifier, the modifier is coated on the surface of the carbonyl iron, thereby reducing the surface energy of the carbonyl iron particles and making the carbonyl iron in a stable state. In addition, the lipophilic group of the modifier forms a spatial flatness on the surface of the carbonyl iron, reducing the phenomenon of particle re-agglomeration, and the absolute resistance group is improved, so that the corrosion potential of the powder moves positively. The dispersibility and corrosion resistance of the modified carbonyl iron are improved. The modifiers contain hydrophobic groups, and the surface contact angle of the modified carbonyl iron is improved, which has hydrophobic properties. DETAILED DESCRIPTION
[0022] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples can be obtained from commercial sources.
[0023] Example 1 Preparation of carbonyl iron: The modifier was dissolved in 200 mL of solvent, and ultrasonically treated for 30 minutes to obtain a surfactant dispersion, and then the carbonyl iron powder was added to the surfactant dispersion, and the mixture was stirred at a constant temperature of 57°C for 1 hour to react, washed with deionized water, and dried at 75°C after separation to obtain prefabricated modified carbonyl iron; polydimethylsiloxane was added to 200 mL of n-heptane, and ultrasonically treated at 60°C for 20 minutes to obtain a mixed solution, and then the prefabricated modified carbonyl iron was added to the mixed solution, and then stirred at 60°C for 1.5 hours, and washed alternately with deionized water and n-heptane three times, and finally dried in an oven at 60°C to obtain modified carbonyl iron; The modifier is glycine, the solvent is deionized water, and the mass ratio of the modifier, carbonyl iron and polydimethylsiloxane is 1:2.1:2.5.
[0024] The core layer includes 0.3% iron, 0.5% copper, 1.4% manganese, 0.1% zirconium, and the balance is aluminum and inevitable impurities.
[0025] The anti-corrosion layer includes 0.5% silicon, 0.01% iron, 1.4% manganese, 4% zinc, 0.01% titanium, 0.07% zirconium, 3.07% magnesium, 0.04% scandium, and the remainder is aluminum and inevitable impurities; among which the iron element comes from the modified carbonyl iron prepared as above.
[0026] The brazing layer is 4343 aluminum alloy.
[0027] Preparation of brazed aluminum alloy composites: (1) The materials of the brazing layer, the core layer, and the anti-corrosion layer are melted and cast respectively according to the proportion, the melting temperature is 760°C, the stirring is performed for 20 minutes, and then the refining and degassing are performed, and the liquid aluminum water hydrogen content is ≤0.15ml / 100g Al at 750°C. Subsequently, the casting is performed at a temperature of 680°C, a casting speed of 40mm / min, a water pressure of 0.1MPa, and a water temperature of 30°C. After the casting is completed, the prepared ingot gate part is sawed and removed by 150mm; (2) The core layer, brazing layer and anti-corrosion layer are milled separately. The milling amount of the two large surfaces of each prefabricated layer is 7.5 mm / each surface. After milling, the thickness of the core layer, brazing layer and anti-corrosion layer after milling is 385 ± 2 mm; (3) The brazing layer and the anti-corrosion layer after milling are heated separately, the heating temperature is 520°C, and the insulation time is 10 hours; then the heated brazing layer and the anti-corrosion layer are hot rolled to obtain a brazing prefabricated layer and an anti-corrosion prefabricated layer, the brazing prefabricated layer is rolled to 52±2mm, and the anti-corrosion prefabricated layer is rolled to 70±2mm, and then cut according to the preparation requirements, placed and cooled naturally; (4) grinding and cleaning the two large surfaces of the core layer, and then stacking the brazing prefabricated layer, the anti-corrosion prefabricated layer and the milled core prefabricated layer in sequence, fixing the brazing layer prefabricated layer and the anti-corrosion layer prefabricated layer on both sides of the core prefabricated layer by argon arc welding, and tying the two ends with steel strips to obtain a composite ingot; (5) cold-pressing the composite ingot in a hot rolling mill, and cold-pressing the middle part of the steel strips at both ends of the composite ingot from the middle to both ends. The cold-pressing rolling speed is 20 m / min, and the rolling speed is adjusted downward by 0.5 mm for each pass, and the rolling is performed for 3 passes; (6) The treated composite ingot is heated to 520° C. and kept warm for 10 h. The composite layer is then rolled into a billet with a thickness of 6.5±0.3 mm by a hot rolling mill. The billet is then rolled in a cold rolling mill according to a pass sequence of 6.5-4.0-2.6-1.6-1.0 mm to obtain a semi-finished coil.
[0028] (7) The semi-finished coil is passed through a rewinding trimming machine to remove the edge cracks and burrs, and the trimming width of each side is 50 mm. After trimming, the semi-finished coil is passed through a cold finishing mill and rolled in a pass sequence of 1.0-0.75-0.58-0.45-0.36-0.28-0.22 mm to obtain a coil with a final finished thickness; (8) Use the bending and straightening machine to clean the oil, aluminum chips and other impurities on the surface of the coil and optimize the overall layout. The cleaning water temperature is 80°C and the cleaning speed is 50m / min; (9) The cleaned coil is annealed in an annealing furnace to H24 state. Under nitrogen protection, the coil temperature is controlled at 250°C and kept warm for 4 hours. After being taken out of the furnace, it is naturally cooled and the preparation is completed after cutting.
[0029] Example 2 Preparation of carbonyl iron: The modifier was dissolved in 200 mL of solvent, and ultrasonically treated for 30 minutes to obtain a surfactant dispersion, and then the carbonyl iron powder was added to the surfactant dispersion, and the mixture was stirred at a constant temperature of 63°C for 2 hours to react, and finally washed with deionized water, separated and dried at 75°C to obtain prefabricated modified carbonyl iron; polydimethylsiloxane was added to 200 mL of n-heptane, and ultrasonically treated at 60°C for 20 minutes to obtain a mixed solution, and then the prefabricated modified carbonyl iron was added to the mixed solution, and then stirred at 60°C for 1.5 hours, and washed with deionized water and n-heptane alternately for three times, and finally dried in an oven at 60°C to obtain modified carbonyl iron; The modifier is glycine, the solvent is deionized water, and the mass ratio of the modifier, carbonyl iron and polydimethylsiloxane is 1:2.2:2.5.
[0030] The core layer includes 0.7% iron, 0.8% copper, 1.8% manganese, 0.15% zirconium, 0.05% magnesium, 0.05% zinc, 0.05% titanium, and the balance is aluminum and inevitable impurities.
[0031] The anti-corrosion layer includes 1.0% silicon, 0.3% iron, 0.1% copper, 1.8% manganese, 5% zinc, 0.03% titanium, 0.12% zirconium, 3.27% magnesium, 0.06% scandium, and the remainder is aluminum and inevitable impurities; among which the iron element comes from the modified carbonyl iron prepared as above.
[0032] The brazing layer is 4045 aluminum alloy.
[0033] Preparation of brazed aluminum alloy composites: (1) The materials of the brazing layer, the core layer, and the anti-corrosion layer are melted and cast respectively according to the proportion, the melting temperature is 780°C, the stirring is performed for 30 minutes, and then the refining and degassing are performed, and the liquid aluminum water hydrogen content is ≤0.15ml / 100g Al at 760°C. Subsequently, the casting is performed at a temperature of 710°C, the casting speed is 60mm / min, the water pressure is 0.2MPa, and the water temperature is 30°C. After the casting is completed, the prepared ingot gate part is sawed and removed by 200mm; (2) The core layer, brazing layer and anti-corrosion layer are milled separately. The milling amount of the two large surfaces of each prefabricated layer is 10 mm / each surface. After milling, the thickness of the core layer, brazing layer and anti-corrosion layer after milling is 385 ± 2 mm; (3) The brazing layer and the anti-corrosion layer after milling are heated separately, the heating temperature is 540°C, and the insulation time is 14h; then the heated brazing prefabricated layer and the anti-corrosion prefabricated layer are hot rolled to obtain the brazing prefabricated layer and the anti-corrosion prefabricated layer, the brazing prefabricated layer is rolled to 52±2mm, and the anti-corrosion prefabricated layer is rolled to 70±2mm, and then they are cut according to the preparation requirements, placed and cooled naturally; (4) The two large surfaces of the core layer are polished and cleaned, and then the brazing prefabricated layer, the anti-corrosion prefabricated layer and the core prefabricated layer are stacked in sequence, and the brazing layer prefabricated layer and the anti-corrosion layer prefabricated layer are fixed on both sides of the core layer prefabricated layer by argon arc welding, and the two ends are tied with steel strips to obtain a composite ingot; (5) cold-pressing the composite ingot in a hot rolling mill, and cold-pressing the middle part of the steel strips at both ends of the composite ingot from the middle to both ends. The cold-pressing rolling speed is 30 m / min, and the rolling speed is adjusted downward by 0.5 mm for each pass, and the rolling is performed for 5 passes; (6) The treated composite ingot is heated to 520° C. and kept warm for 10 h. The composite layer is then rolled into a billet with a thickness of 6.5±0.3 mm by a hot rolling mill. The billet is then rolled in a cold rolling mill according to a pass sequence of 6.5-4.0-2.6-1.6-1.0 mm to obtain a semi-finished coil.
[0034] (7) The semi-finished coil is passed through a rewinding trimming machine to remove the edge cracks and burrs, and the trimming width of each side is 80 mm. After trimming, the semi-finished coil is passed through a cold finishing mill and rolled in a pass sequence of 1.0-0.75-0.58-0.45-0.36-0.28-0.22 mm to obtain a coil with a final finished thickness; (8) Use the tension and bending straightening machine to clean the oil, aluminum chips and other impurities on the surface of the coil, and optimize the overall layout. The cleaning water temperature is 80°C and the cleaning speed is 100m / min; (9) The cleaned coil is annealed to H24 state in an annealing furnace. Under nitrogen protection, the coil temperature is controlled at 280°C for 5 hours. After being taken out of the furnace, it is naturally cooled and the preparation is completed after cutting.
[0035] Example 3 Preparation of carbonyl iron: The modifier was dissolved in 200 mL of solvent, and ultrasonically treated for 30 minutes to obtain a surfactant dispersion, and then the carbonyl iron powder was added to the surfactant dispersion, and the mixture was stirred at a constant temperature of 60°C for 1.5 hours to react, and finally washed with deionized water, separated and dried at 75°C to obtain prefabricated modified carbonyl iron; polydimethylsiloxane was added to 200 mL of n-heptane, and ultrasonically treated at 60°C for 20 minutes to obtain a mixed solution, and then the prefabricated modified carbonyl iron was added to the mixed solution, and then stirred at 60°C for 1.5 hours, and washed with deionized water and n-heptane alternately for three times, and finally dried in an oven at 60°C to obtain modified carbonyl iron; The modifier is glycine, the solvent is deionized water, and the mass ratio of the modifier, carbonyl iron and polydimethylsiloxane is 1:2.15:2.5.
[0036] The core layer includes 0.5% of iron, 0.65% of copper, 1.6% of manganese, 0.125% of zirconium, 0.025% of magnesium, 0.025% of zinc, 0.025% of titanium, and the balance is aluminum and inevitable impurities.
[0037] The anti-corrosion layer includes 0.75% silicon, 0.2% iron, 0.05% copper, 1.6% manganese, 4.5% zinc, 0.02% titanium, 0.1% zirconium, 3.17% magnesium, 0.05% scandium, and the remainder is aluminum and inevitable impurities; among which the iron element comes from the modified carbonyl iron prepared as above.
[0038] The brazing layer is 4343 aluminum alloy.
[0039] Preparation of brazed aluminum alloy composites: (1) The materials of the brazing layer, the core layer, and the anti-corrosion layer are melted and cast respectively according to the proportion, the melting temperature is 770°C, and the materials are stirred for 25 minutes, and then refined and degassed, and refined for 25 minutes at 755°C until the liquid aluminum water hydrogen content is ≤0.15ml / 100g Al, and then cast at a temperature of 680°C, a casting speed of 50mm / min, a water pressure of 0.15MPa, and a water temperature of 30°C. After the casting is completed, the prepared ingot gate part is sawed and removed by 175mm; (2) The core layer, brazing layer and anti-corrosion layer are milled separately. The milling amount of the two large surfaces of each prefabricated layer is 8.7 mm / each surface. After milling, the thickness of the core layer, brazing layer and anti-corrosion layer after milling is 385 ± 2 mm; (3) The brazing layer and the anti-corrosion layer after milling are heated separately, the heating temperature is 530°C, and the insulation time is 12 hours; then the heated brazing layer and the anti-corrosion layer are hot rolled to obtain a brazing prefabricated layer and an anti-corrosion prefabricated layer, the brazing prefabricated layer is rolled to 52±2mm, and the anti-corrosion prefabricated layer is rolled to 70±2mm, and then cut according to the preparation requirements, placed and cooled naturally; (4) grinding and cleaning the two large surfaces of the core layer, and then stacking the brazing prefabricated layer, the anti-corrosion prefabricated layer and the milled core prefabricated layer in sequence, fixing the brazing layer prefabricated layer and the anti-corrosion layer prefabricated layer on both sides of the core prefabricated layer by argon arc welding, and tying the two ends with steel strips to obtain a composite ingot; (5) cold-pressing the composite ingot in a hot rolling mill, and cold-pressing the middle part of the steel strips at both ends of the composite ingot from the middle to both ends. The cold-pressing rolling speed is 25 m / min, and the rolling is adjusted downward by 0.5 mm for each pass, and 4 passes are performed; (6) The treated composite ingot is heated to 530° C. and kept warm for 12 h. The composite layer is then rolled into a billet with a thickness of 6.5±0.3 mm by a hot rolling mill. The billet is then rolled in a cold rolling mill according to a pass sequence of 6.5-4.0-2.6-1.6-1.0 mm to obtain a semi-finished coil.
[0040] (7) The semi-finished coil is passed through a rewinding trimming machine to remove the edge cracks and burrs, and the trimming width of each side is 65 mm. After trimming, the semi-finished coil is passed through a cold finishing mill and rolled in a pass sequence of 1.0-0.75-0.58-0.45-0.36-0.28-0.22 mm to obtain a coil with a final finished thickness; (8) Use the bending and straightening machine to clean the oil, aluminum chips and other impurities on the surface of the coil, and optimize the overall layout. The cleaning water temperature is 80°C and the cleaning speed is 75m / min; (9) The cleaned coil is annealed to H24 state in an annealing furnace. Under nitrogen protection, the coil temperature is controlled at 265°C for 4.5 hours. After being taken out of the furnace, it is naturally cooled and the preparation is completed after cutting.
[0041] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in the preparation of the modified carbonyl iron, the mass ratio of the modifier, carbonyl iron and polydimethylsiloxane is 1:1.9:2.5.
[0042] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in the preparation of the modified carbonyl iron, the mass ratio of the modifier, carbonyl iron and polydimethylsiloxane is 1:2.4:2.5.
[0043] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in the preparation of modified carbonyl iron, the modifier is hexadecyltrimethylammonium bromide.
[0044] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in the preparation of modified carbonyl iron, the modifier is sodium dodecylbenzene sulfonate.
[0045] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that the reaction time is 0.5 h when the prefabricated modified carbonyl iron is prepared.
[0046] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that the reaction time is 3 hours when the prefabricated modified carbonyl iron is prepared.
[0047] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that the reaction temperature is 50°C when the prefabricated modified carbonyl iron is prepared.
[0048] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that the reaction temperature is 70°C when the prefabricated modified carbonyl iron is prepared.
[0049] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that the content of magnesium in the anti-corrosion layer is 2.77%, and the content of scandium is 0.02%.
[0050] Embodiment 13 Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that the content of magnesium in the anti-corrosion layer is 3.57%, and the content of scandium is 0.08%.
[0051] Comparative Example 1 Comparative Example 1 is based on Example 3, and magnesium and scandium are not added to the anti-corrosion layer in Comparative Example 1.
[0052] Comparative Example 2 Comparative Example 2 is based on Example 3, and the modified carbonyl iron in Comparative Example 2 is not treated with polydimethylsiloxane.
[0053] Comparative Example 3 Comparative Example 3 is based on Example 3, and the source of iron in the anti-corrosion layer of Comparative Example 3 is ordinary unmodified carbonyl iron.
[0054] Comparative Example 4 Comparative Example 4 is based on Example 3. In Comparative Example 4, when preparing the brazing aluminum alloy composite material, the middle part of the steel strips bundled at both ends of the composite layer is not cold rolled.
[0055] Performance testing The following performance tests were performed on the samples of Examples 1-13 and Comparative Examples 1-4: (1) Corrosion resistance test Using "GB / T 10125-2021 Artificial atmosphere corrosion test, salt spray test" as the test standard, the corrosion resistance of the samples was tested. Each sample was tested 3 times, the average value was taken and the test results were filled in Table 1.
[0056] (2) Tensile strength test before and after brazing Using GB / T 228.1-2021 as the test standard, the tensile strength of the samples before and after brazing was tested. The brazing process was 605℃ and the temperature was kept at 5min. Three samples were taken for each example or comparative example for testing, and the average value was taken. The test results were filled in Table 1.
[0057] Table 1 Performance test results of Examples 1-13 and Comparative Examples 1-4 Data analysis Combined with Table 1, it can be seen that the CASS salt spray of Examples 1-3 is 220h or more, so the brazing aluminum alloy composite material prepared in the present application has good corrosion resistance. The tensile strength of Examples 1-3 before brazing is 215MPa or more, and the tensile strength after brazing is 175MPa or more, indicating that the brazing aluminum alloy composite material prepared in the present application has good tensile strength.
[0058] In Examples 4 and 5, when preparing modified carbonyl iron, the mass ratio of the modifier to the carbonyl iron is not within the range specified in the present application. When the content of the modifier is too little, the surface of the carbonyl iron powder is loose and it is difficult to further improve the density. Therefore, the binding performance of the carbonyl iron is difficult to further improve, and the stability is reduced. At the same time, it also affects the corrosion resistance of the anti-corrosion layer. When the content of the modifier is too much, it affects the overall stability of the system, and it is difficult to promote the formation of a dense modified layer on the surface of the carbonyl iron. Therefore, the performance of the prepared anti-corrosion layer is reduced, and the tensile strength of the anti-corrosion layer is also affected. Therefore, the corrosion resistance and tensile strength of Examples 4 and 5 are both reduced.
[0059] In Example 6 and Example 7, when preparing modified carbonyl iron, the modifiers were replaced with hexadecyltrimethylammonium bromide and sodium dodecylbenzenesulfonate, respectively. The complex impedance of hexadecyltrimethylammonium bromide and sodium dodecylbenzenesulfonate after modification was difficult to significantly improve, so the corrosion resistance of Example 6 and Example 7 was significantly reduced.
[0060] In Examples 8 and 9, when preparing modified carbonyl iron, the reaction time is not within the range specified in the present application. When the reaction time is too short, the coverage rate on the surface of the carbonyl iron is too small, and it is difficult to evenly form a stable modified layer, and the modification effect is difficult to further improve, which affects the stability of the modified carbonyl iron. When the reaction time is too long, the carbonyl iron powder is oxidized by glycine, which reduces the corrosion resistance of the modified carbonyl iron and also affects the mechanical strength of the anti-corrosion layer. Therefore, the corrosion resistance of Examples 8 and 9 is reduced, and the tensile strength is also affected.
[0061] In Examples 10 and 11, when preparing modified carbonyl iron, the reaction temperature is not within the range specified in the present application. When the reaction temperature is too low, the molecular thermal motion speed in the system is too slow, the collision rate between glycine and carbonyl iron in the system decreases, and the glycine molecules are difficult to graft onto the surface of the carbonyl iron powder. It is difficult to form a uniform and dense modified layer, and the corrosion resistance of the anti-corrosion layer is difficult to improve. At the same time, it will also affect the tensile strength of the anti-corrosion layer. When the reaction temperature is too high, the molecular thermal motion speed in the system is too fast, the collision frequency in the system is too large, and the glycine molecules form an irregular coating layer on the surface of the carbonyl iron powder. It is also difficult to form a uniform and dense modified layer. Therefore, the stability is reduced, the anti-corrosion performance of the anti-corrosion layer is difficult to improve, and the tensile strength is also affected. Therefore, the corrosion resistance and tensile strength of Examples 10 and 11 are both reduced.
[0062] The contents of magnesium and scandium in Example 13 and Example 14 are not within the range specified in the present application. When the contents of magnesium and scandium are too much or too little, it is difficult for them to further combine with the zinc in the system to form a stable oxide film. Therefore, the stability and corrosion resistance of the anti-corrosion layer are reduced. Therefore, the performance of Example 13 and Example 14 is reduced.
[0063] In Comparative Example 1, there is no magnesium and scandium elements in the anti-corrosion layer, and it is difficult to combine with zinc in the system to form a dense oxide film, and it is difficult to further improve the anti-corrosion performance of the anti-corrosion layer. At the same time, it is difficult to further improve the mechanical properties of the anti-corrosion layer without magnesium elements, and the stability of the prepared anti-corrosion layer is difficult to further improve. Therefore, the corrosion resistance and tensile strength of Comparative Example 1 are both reduced.
[0064] In Comparative Example 2, the carbonyl iron was not treated with polydimethylsiloxane, and it was difficult to further coat the surface of the carbonyl iron, and it was difficult to improve the corrosion resistance and stability. The decreased stability would also affect the overall mechanical strength of the system, and the tensile strength would decrease, so the performance of Comparative Example 2 decreased.
[0065] In Comparative Example 3, the source of iron in the anti-corrosion layer is replaced with ordinary unmodified carbonyl iron. The corrosion resistance of the unmodified carbonyl iron is severely reduced, and the stability is difficult to further improve, and the tensile strength is affected. Therefore, the performance of Comparative Example 1 is reduced.
[0066] In Comparative Example 4, when preparing the brazing aluminum alloy composite material, the middle part of the steel strips bundled at both ends of the composite layer was not cold rolled, and the bonding performance between the brazing layer, the core layer and the anti-corrosion layer was difficult to be further improved, and an offset phenomenon occurred, which affected the stability of the aluminum alloy composite material. In addition, the air in the middle of the composite layer was difficult to be completely discharged, bubbles were formed in the composite layer, and the quality of the finished product was reduced.
[0067] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A high-strength and high-corrosion-resistant brazing aluminum alloy composite material for a radiator, characterized in that: It includes a brazing layer, a core layer and an anti-corrosion layer which are arranged in sequence, wherein the core layer includes the following elemental components in weight percentage: iron 0.3-0.7%, copper 0.5-0.8%, manganese 1.4-1.8%, zirconium 0.1-0.15%, magnesium ≤0.05%, zinc ≤0.05%, titanium ≤0.05%, and the balance is aluminum and inevitable impurities; the anti-corrosion layer includes the following elemental components in weight percentage: silicon 0.5-1.0%, iron 0.2-0.3%, copper 0-0.1%, manganese 1.4-1.8%, zinc 4.0-5.0%, titanium 0.01-0.03%, zirconium 0.07-0.12%, and the balance is aluminum and inevitable impurities.
2. The high-strength and high-corrosion-resistant brazing aluminum alloy composite material for radiator according to claim 1, characterized in that: The iron element in the anti-corrosion layer comes from carbonyl iron, and the carbonyl iron is prepared by modification. The modification method of the carbonyl iron comprises the following steps: The modifier is dissolved in a solvent, subjected to ultrasonic treatment to obtain a surfactant dispersion, carbonyl iron powder is added to the surfactant dispersion, stirred at a certain temperature for a certain time to react, washed and dried to obtain prefabricated modified carbonyl iron; polydimethylsiloxane is added to n-heptane, subjected to ultrasonic treatment to obtain a mixed solution, and then the prefabricated modified carbonyl iron is added to the mixed solution, stirred, washed and dried to obtain modified carbonyl iron.
3. The high-strength and high-corrosion-resistant brazing aluminum alloy composite material for radiator according to claim 2, characterized in that: The modifier includes any one of hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate and glycine.
4. The high-strength and high-corrosion-resistant brazing aluminum alloy composite material for radiator according to claim 2, characterized in that: The mass ratio of the modifier, carbonyl iron and polydimethylsiloxane is 1:(2.1-2.2):2.
5.
5. The high-strength and high-corrosion-resistant brazing aluminum alloy composite material for radiator according to claim 2, characterized in that: The reaction time for preparing the prefabricated modified carbonyl iron is 1-2 hours.
6. The high-strength and high-corrosion-resistant brazing aluminum alloy composite material for radiator according to claim 2, characterized in that: The reaction temperature during the preparation of the prefabricated modified carbonyl iron is 57-63°C.
7. The high-strength and high-corrosion-resistant brazing aluminum alloy composite material for radiator according to claim 2, characterized in that: The anti-corrosion layer also includes the following elements in percentage by weight: 1.07-1.27% magnesium and 0.04-0.06% scandium.
8. A method for preparing a high-strength and high-corrosion-resistant brazing aluminum alloy composite material for a radiator as claimed in any one of claims 1 to 7, characterized in that: The steps include: The materials of the brazing layer, the core layer and the anti-corrosion layer are melt-casted according to the proportion, and then milled respectively after melting and casting. The milled brazing layer and the anti-corrosion layer are heated respectively, and then hot-rolled respectively to obtain the brazing prefabricated layer and the anti-corrosion prefabricated layer respectively. After cooling, the brazing prefabricated layer, the core prefabricated layer and the anti-corrosion layer are stacked in sequence, and the brazing layer prefabricated layer and the anti-corrosion layer prefabricated layer are fixed on both sides of the core layer prefabricated layer by argon arc welding, and the two ends are tied with steel strips to obtain a composite ingot; the composite ingot is rolled in a hot rolling mill, and then rolled by a cold rolling mill to obtain a semi-finished coil, the edge cracks, burrs and other parts of the semi-finished coil are cut off, and then rolled again by a cold finishing mill to obtain a coil of the final finished thickness, and then the coil surface is cleaned of oil, dirt and debris by a stretch bending and straightening machine, and finally annealed in an annealing furnace, and cut after cooling to obtain an aluminum alloy composite material.
9. The method for preparing a high-strength and high-corrosion-resistant brazing aluminum alloy composite material for a radiator according to claim 8, characterized in that: The rolling process of the composite ingot in a hot rolling mill specifically comprises the following steps: The middle part of the steel strips bundled at both ends of the composite layer is cold pressed, and the cold pressing direction is from the middle to both ends, wherein the cold pressing rolling speed is 20-30m / min, and the rolling is performed 3-5 times.
Citation Information
Patent Citations
Brazing material for automatic brazing as well as preparation method and application thereof
CN111250892A
Multi-layer composite aluminum alloy for water cooling plate and preparation method of multi-layer composite aluminum alloy
CN117246003A
High strength aluminium alloy brazing sheet, brazed assembly and method for producing the same
CN1832825A
Refractory metal diffusion bonding
GB1132348A
High strength aluminium alloy brazing sheet, brazed assembly and method for producing same
US20050079376A1